Efficiency Enhancement in Transportation for Trading Business in Thailand - Jarutirasarn, Piyachat (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this research were 1) to study factors affecting the transportation efficiency of carrier entrepreneurs providing transportation services in trading business, 2) to study the environment, problems and obstacles of the entrepreneurs and 3) to study the approaches to increase the transportation efficiency of the entrepreneurs. The sample group used in this research is the carrier entrepreneurs that provide transportation services in the business of trading and also have their establishments in located in the 4 regions of Thailand in the total of 400 people. These people were obtained through quota sampling and the tools used to collect data are the questionnaires prepared by the author which have the content validity between 0.67-1.00 and the reliability of the questionnaire was between 0.70- 0.90. The data were analyzed using percentage, average, standard deviation and one-way Analysis of Variance. The testing of the differences in pairs was carried out by LSD method and the multiple regression was analyzed by Enter method. The research results revealed as follows: 1. Factors affecting the transportation efficiency of the transportation service providers in the trading business are the number of personnel and the time of operation. It was found that most of the samples had employees in the organization of less than 11 people and the duration of business operation was less than 3 years 2. For the environment, problems and obstacles of the transport operators who provide goods transportation services in the trading business, it was found that the transportation service environment consisting of transportation knowledge and perspective on transportation development and service standards affected the highest satisfaction to customers, followed by transportation with no pollution to the environment, having planning, system management and work control in every time for moving products from one location to another. The respondents responded to questionnaires about transport efficiency made us aware of problems, obstacles to transportation operators that provide transportation services in trading business. It was found that the number of customers, the number of cars, tools and technology, the cost of transportation development had an effect on transportation efficiency at a high level. 3. Ways to improve transportation efficiency in order to improve transportation efficiency, it should be focused on the break-even point in operations, taken into consideration on the factors of communication infrastructure, creating cooperation of the loading and unloading system and the construction of a transport terminal. Technologies should be integrated in transportation in order to meet the needs of customers as much as possible. Article history: Received 3 November 2019 Revised 20 December 2019 Accepted 23 December 2019 SIMILARITY INDEX = 0.00 %